Pengaruh Teknologi Digital Dalam Perkembangan Layanan Perbankan Syariah - Priska Cintya; Fauzatul Laily Nisa (CV. ALIM'SPUBLISHING, 2024)
Digital transformation has become an important issue in the financial industry, including Islamic banking in the current digital era. The development of digital technology has affected the way Islamic banks provide services to customers, allowing them to reach more customers in various locations without being limited by physical offices. Digital banking services developed using digital technology provide convenience, speed, and security in transactions to customers. This study aims to examine the influence of digital technology in the development of Islamic banking services. The money research method used is a literature study by analyzing various literature sources. The results show that digital transformation in Islamic banking has a significant impact, including increased efficiency, productivity, service quality, and customer satisfaction.